Antifungal susceptibility of Malassezia furfur, Malassezia sympodialis, and Malassezia globosa to azole drugs and amphotericin B evaluated using a broth microdilution method - Rojas, Florencia Dinorah (2014)
Fil: Rojas, Florencia Dinorah. Universidad Nacional del Nordeste. Instituto de Medicina Regional; Argentina.